1999
DOI: 10.1111/1469-7610.00539
|View full text |Cite
|
Sign up to set email alerts
|

The Orphans of Eritrea: A Five‐year Follow‐up Study

Abstract: A group of 4-7-year-old war orphans were examined for the first time while living in an institution (the Solomuna Orphanage) during a protracted war between Eritrea and Ethiopia. At that time, they were compared to a group of refugee children living in a nearby camp with one or both parents. The orphans exhibited significantly more behavioral symptoms than the refugee children, but performed the cognitive tests at a more advanced level. Five years later, the orphans were re-examined; and they were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 19 publications
3
46
0
8
Order By: Relevance
“…For example, children who were evacuated during the Second World War bombings of London showed more distress than those who stayed with their parents and were directly exposed to the war (Foster, Davies and Steele, 2003;Freud and Burlingham, 1943). Similarly, a study of young children exposed to war in Eritrea, found that children who lived in orphanages showed more signs of emotional distress five years later than those who lived in a refugee camp with one or both parents (Wolff and Fesseha, 1999).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, children who were evacuated during the Second World War bombings of London showed more distress than those who stayed with their parents and were directly exposed to the war (Foster, Davies and Steele, 2003;Freud and Burlingham, 1943). Similarly, a study of young children exposed to war in Eritrea, found that children who lived in orphanages showed more signs of emotional distress five years later than those who lived in a refugee camp with one or both parents (Wolff and Fesseha, 1999).…”
mentioning
confidence: 97%
“…Research suggests that children also benefit from participation in decisions that affect their lives. For example, Wolff and Fesseha (1999) compared the mental health of war orphans living in two different orphanages in Eritrea, one in which the children were expected to participate in its activities and another where the director made all of the decisions and daily routines were determined by explicit roles and schedules. They found that children in the first institution showed fewer behavioural symptoms of emotional distress than those living in the second.…”
mentioning
confidence: 99%
“…Somando-se a isso, as instituições que acolhem crianças, principalmente as do tipo residencial, podem motivar as crianças a compartilharem tarefas e a cooperarem entre si e com os funcioná-rios 11 . Esse tipo de atitude por parte dos educadores pode contribuir na prevenção de efeitos traumáticos gerados pela convivência, precoce e prolongada, em instituições asilares 11 .…”
Section: Percepções Das Educadoras Acerca Do Trabalho Com Crianças Inunclassified
“…Esse tipo de atitude por parte dos educadores pode contribuir na prevenção de efeitos traumáticos gerados pela convivência, precoce e prolongada, em instituições asilares 11 .…”
Section: Percepções Das Educadoras Acerca Do Trabalho Com Crianças Inunclassified
See 1 more Smart Citation